RECOMMENDATIONS FOR THE DESIGN OF REHABILITATION CENTERS FOR THE ELDERLY, BASED ON THE EXAMPLE OF CHINA - Hongjuan, Zhao (Theory and practice of design, 2024)
Purpose – to develop recommendations for the design of rehabilitation centers for the elderly, using the example of China. Methodology: based on the method of complex functional and structural analysis, statistical; morphological; historical; dialectical; factual; comparative analysis of natural, graphical and statistical data; expert assessments; comprehensive analysis of scientific research; functional-spatial modeling; artistic and compositional; economic analysis according to the criteria of feasibility of choice, system analysis. Results. On the basis of system analysis, a structural model of the formation of the internal space of a rehabilitation center for the elderly has been developed, and the directions of the architectural and planning organization of institutions have been determined. This helps to solve the complex formation, miscalculation of the prospects for development, improvement, comfort, level of medical care, and efficiency of the center. A methodological assessment of the factors influencing the architectural and planning organization of the rehabilitation center is provided. The principles and methods of architectural and planning organization of the rehabilitation center environment are formed. The main aspects of optimizing a balanced, harmoniously holistic, ergonomic, psychologically comfortable, and recreational architectural environment are identified. Urban planning location of rehabilitation center for the elderly: city center, suburbs and recreational areas. The main requirements for spatial and territorial organization are defined: accessibility and barrier-free environment; adaptability of the external space; ensuring sanitary and hygienic requirements; maintaining functional connection between the blocks; distribution of flows of elderly people, technical and medical personnel; introduction of additional rehabilitation spaces; laying the foundation for the prospects of the institution’s development. The spatial-territorial organization of the rehabilitation center sites is proposed. The main functional zones and their content are determined. The main compositional solutions for the spatial-territorial arrangement of the rehabilitation center blocks are identified. Scientific novelty. The article, which is part of the dissertation research, analyzes Chinese and foreign rehabilitation centers for the elderly, reveals current issues, imperfections in the architectural and construction regulatory framework, which does not take into account all the volumes and features of such institutions, their number of storeys, location, arrangement, layout and equipment. The study provides up-to-date methodological recommendations for improving the existing architectural and planning organization of residential centers for the elderly. This work will also help to improve the Ukrainian regulatory framework for this complex issue. Practical relevance. Optimal placement of rehabilitation center. in the structure of cities; placement of rehabilitation center – compliance with the latest but improved standards; urban planning placement of RC in the structure of the city: location and accessibility; proximity to medical facilities, quick assistance in emergency situations; provision of recreation areas and green spaces; ensuring barrier-free access to all premises and areas of the center, including ramps and elevators; placement of rehabilitation center near other medical facilities, sports complexes, cultural institutions to promote integration and cooperation.